2·c·x-c·y-6·x+3·y=(2·x-y)·(с-3)
56·p·q-1-7·q+8·p=(7·q+1)·(8·p-1)
7·x·y-x²-x+7·y=(x+1)·(7·y-x)
b³-b²+b-1=(b-1)·(b²+1)
y⁵-y³+y²-1=(y-1)·(y+1)·(y+1)·(y²-y+1)
Объяснение:
2·c·x-c·y-6·x+3·y=с·(2·x-y)-3·(2·x-y)=(2·x-y)·(с-3)
56·p·q-1-7·q+8·p=56·p·q+8·p-1-7·q=8·p·(7·q+1)-1·(1+7·q)=(7·q+1)·(8·p-1)
7·x·y-x²-x+7·y=7·x·y+7·y-(x²+x)=7·y(x+1)-x·(x+1)=(x+1)·(7·y-x)
b³-b²+b-1=b²·(b-1)+1·(b-1)=(b-1)·(b²+1)
y⁵-y³+y²-1=y³·(y²-1)+1·(y²-1)=(y²-1)·(y³+1)=(y-1)·(y+1)·(y+1)·(y²-y+1)
b⁸+3·b⁵-2·b-6=b⁵(b³+3)-2(b+3)=...
В последнем выражении что-то не хватает
Объяснение:
вроде бы все правильно)